Novel kidney injury biomarkers in tropical infections: a review of the literature - Meneses, Gdayllon Cavalcante; Silva Junior, Geraldo Bezerra da; Tôrres, Paulo Pacelli Bezerra Filizola; Castro, Valeska Queiroz de; Lopes, Renata Lima; Martins, Alice Maria Costa; Daher, Elizabeth De Francesco (Revista do Instituto de Medicina Tropical de São Paulo, 2020)
Tropical diseases are mainly found in the tropical regions of Asia, Africa and Latin America. They are a major Public Health problem in these regions, most of them are considered neglected diseases and remain as important contributors to the development of AKI (Acute Kidney Injury), which is associated with increased patients’ morbidity and mortality. In most countries, kidney disease associated to tropical diseases is attended at health services with poor infrastructure and inadequate preventive measures. The long‑term impacts of these infections on kidney tissue may be a main cause of future kidney disease in these patients. Therefore, the investigation of novel kidney injury biomarkers in these tropical diseases is of utmost importance to explain the mechanisms of kidney injury, to improve their diagnosis and prognosis, as well as the assessment to health systems by these patients. Since 2011, our group has been studying renal biomarkers in visceral and cutaneous leishmaniasis, schistosomiasis, leptospirosis and leprosy. This study has increased the knowledge on the pathophysiology of kidney disease in the presence of these infections and has contributed to the early diagnosis of kidney injury, pointing to glomerular, endothelial and inflammatory involvement as the main causes of the mechanisms leading to nephropathy and clinical complications. Future perspectives comprise establishing longterm cohort groups to assess the development of kidney disease and the patients’ survival, as well as the use of new biomarkers such as urinary exosomes to detect risk groups and to understand the progression of kidney injuries.